Pengaruh Islamic Law System Terhadap Peluang Pemberlakuan Mediasi Penal dalam Pembaharuan Hukum Pidana Indonesia - Ghofarrozin, Abdul; Janah, Tutik Nurul (Universitas Nurul Jadid, 2021)
This research is normative juridical research. This research is a research library that explores data on legislation and articles on the influence of Islamic law system and opportunities for penal mediation in reformulation of Indonesian criminal law. Basically, penal mediation has not been regulated in the Indonesian penal justice system, except for special criminal cases. For example, criminal matters with juvenile justice system. But in general, the Indonesian criminal justice system is not yet familiar with penal mediation. Penal justice system is usually decided by imprisonment or imprisonment and fines. The Indonesian legal system recognizes only mediation in civil law.This is different from the concept of criminalization in Islamic law. Fiqh jinayah or Islamic criminal law has options in the settlement of criminal cases. That is by choosing qishas or al shulhu (peace). The influence of Islamic law system in Indonesian legal system can be realized from the rules on family law in KHI and Sharia economic law.This influence opens up opportunities for regulations on penal mediation in the reformulation of Indonesian criminal law. And just like family law in KHI which is not adopted textually from Islamic law into positive law of Indonesia. So it should be in the application of penal mediation. Penal mediation becomes a new hope in reformulation or reform of criminal law in Indonesia.Keywords: Islamic Law Sytem, Penal Mediation, Criminal Law Reform.